2010
DOI: 10.1089/scd.2009.0065
|View full text |Cite
|
Sign up to set email alerts
|

Cdk2 Inhibition Prolongs G1 Phase Progression in Mouse Embryonic Stem Cells

Abstract: Embryonic stem cells (ESCs) proliferate rapidly and have a unique cell-cycle structure with a very short G1 phase. Previous reports suggested that the rapid G1 phase progression of ESCs might be underpinned by high and precocious Cdk2 activity and that Cdk2 activity might be crucial for both cell-cycle regulation and cell-fate decisions in human ESCs. However, the actual role of Cdk2 in cell-cycle progression of mouse ESCs (mESCs) has not been elucidated. In this study, we investigated the effects of down-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 35 publications
3
56
0
Order By: Relevance
“…1A to C). We enriched cultures for mitotic cells by treating them with nocodazole (200 ng/ml, 16 h), a widely used synchronizing agent that has been successfully employed to synchronize ESCs (19)(20)(21)(22). Cells in G 1 were purified 1 h after release of the nocodazole block.…”
Section: Resultsmentioning
confidence: 99%
“…1A to C). We enriched cultures for mitotic cells by treating them with nocodazole (200 ng/ml, 16 h), a widely used synchronizing agent that has been successfully employed to synchronize ESCs (19)(20)(21)(22). Cells in G 1 were purified 1 h after release of the nocodazole block.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, they are potentially useful because they produce acute effects, and the dose-response range can easily be explored. Several groups have previously used small molecules (e.g., roscovitine) targeted to CDKs but with a host of off-target effects on ESCs and found drastically different results on promoting differentiation (17,20). To explore the effects of these small molecule inhibitors further, we applied both roscovitine and CVT-313, a more specific CDK2 inhibitor, to ESCs.…”
Section: Knockdown Of Cdk2 or Cyclin A With Sirna Reduces The Prolifementioning
confidence: 99%
“…Furthermore, it was later shown that knockout mice of CDK2, the main CDK thought to be responsible for G1/S progression in ESCs, were viable and therefore presumably did not prematurely differentiate their stem cells (18,19). In contrast, it was recently reported that olomoucine II, another CDK inhibitor, could induce mRNA up-regulation of differentiation markers in mouse ESCs and that CDK2 siRNA could induce morphology changes characteristic of differentiation (20). In human ESCs exposure to roscovitine and other CDK inhibitors sometimes led to a loss of pluripotency markers but other times did not (21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Functional studies addressing the interaction between cell cycle phase and differentiation in ESCs have been based primarily on manipulations of genes associated with cell cycle regulation, particularly CDK2 [10][11][12], p21 [13,14], p27 [15], and hTERT [16] (reviewed in [17]). Constitutive activity of CDK2 and CyclinE [7,11,12] in ESCs is important for their shortened G1 phase.…”
Section: Introductionmentioning
confidence: 99%
“…Constitutive activity of CDK2 and CyclinE [7,11,12] in ESCs is important for their shortened G1 phase. Several studies in mouse and human ESCs showed that inhibition of CDK2 leads to cell cycle arrest in G1 and subsequent differentiation to extraembryonic lineages [11][12][13]. This differentiation, however, does not necessarily reflect increased propensity to differentiate in G1.…”
Section: Introductionmentioning
confidence: 99%